(untitled) (Research, Society and Development, 2020)
Cocona (Solanum sessiliflorum Dunal) is a tropical fruit with different physicochemical and nutritional characteristics, slightly acidic and exotic flavor, with applicability in the food area is limited. The research is experimental and descriptive, in a qualitative and quantitative approach with cross-sectional design. The objective of the present research was to develop a cake enriched with cocona flour in order to provide a better use of the fruit in regional cuisine, as well as add nutritional value to this preparation. It was possible to verify that the partial replacement of wheat flour by cocona flour in chocolate cakes proved to be a promising alternative, considering the good nutritional and sensorial characteristics of the product obtained in the physicochemical and sensorial tests. Additionally, it can be concluded that manna-cubiu flour is a potential ingredient to add nutritional value to traditional recipes, besides favoring the optimization of fruit consumption in an alternative way for the population.